1977
DOI: 10.1098/rspb.1977.0096
|View full text |Cite
|
Sign up to set email alerts
|

Structural requirements for opioid activity of analogues of the enkephalins

Abstract: Structure-activity relations of a series of analogues of the two endo­genous morphine-like peptides, leucine-enkephalin and methionine-enkephalin are examined on the basis of ( a ) effects on the mouse vas deferens and the guinea pig ileum and ( b ) affinities for the rat brain opiate receptor. In the mouse vas deferens, metabolism of the peptides by proteolysis is not a major influence on activity. In contrast, however, brain opiate re­ceptor preparations contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Compounds 3, 4, and 6 were found to bind DOPR with modest affinity, a finding consistent with our observation that these compounds were less efficient than Leu 5 -enkephalin and compound 1 at promoting DOPR internalization (Figures 6 and 7) and ERK1/2 phosphorylation (Figure 8 -enkephalin strongly reduces its affinity and activity for DOPR (17,18). In fact, it is known that the phenyl side chain of the L-Phe 4 residue of Leu 5 -enkephalin is critical for its biological activity (17) and that Leu -enkephalin were shown to bind and activate DOPR similarly (17,18). Still, the slightly better affinity of compound 6 led us to hypothesize that this compound contains a D-Leu at position 5 while compound 4 contains an L-Leu at the same position.…”
Section: Binding Properties Of Enkephalin Derivativessupporting
confidence: 76%
See 3 more Smart Citations
“…Compounds 3, 4, and 6 were found to bind DOPR with modest affinity, a finding consistent with our observation that these compounds were less efficient than Leu 5 -enkephalin and compound 1 at promoting DOPR internalization (Figures 6 and 7) and ERK1/2 phosphorylation (Figure 8 -enkephalin strongly reduces its affinity and activity for DOPR (17,18). In fact, it is known that the phenyl side chain of the L-Phe 4 residue of Leu 5 -enkephalin is critical for its biological activity (17) and that Leu -enkephalin were shown to bind and activate DOPR similarly (17,18). Still, the slightly better affinity of compound 6 led us to hypothesize that this compound contains a D-Leu at position 5 while compound 4 contains an L-Leu at the same position.…”
Section: Binding Properties Of Enkephalin Derivativessupporting
confidence: 76%
“…The Tyr-Gly-Gly-Phe//D-Leu stereochemistry was attributed to 6 because it is slightly more active than 4, similar to TyrGly-Gly-Phe-D-Leu, which is more active toward DOPR than Leu 5 -enkephalin (cf. Table 1) (17,18). Admittedly, this assumption is only based on comparative binding and activity with previous studies and remains to be confirmed by X-ray analysis.…”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…The high to moderate binding affinity and bioactivity for the opioid receptors are surprising since it was found that D-aromatic amino acid residues in this position resulted in inactive peptides. 19,30 Two strategies were combined to obtain the desired effect of increased binding at opioid receptors and at CCK receptors. Since substitution with D-Trp 4 successfully resulted in an antagonist effect at the CCK-1 receptor, and substitution with Nle 5 resulted in a balanced binding affinity between CCK-1 and CCK-2, a double substitution was attempted to obtain additive result.…”
Section: Binding and Functional Activity Datamentioning
confidence: 99%